PROFIL PEMECAHAN MASALAH LUAS PERMUKAAN DAN VOLUME TABUNG KELAS IX B SISWA SMP NEGERI 1 LORE TENGAH: Profil of Problem Solving of Surface Area and Tube Volume of Class IX B Students SMP Negeri 1 Lore Tengah - SOMPO, DHEVID DHIFKY REONALD; Murdiana, I Nyoman; Karniman, Tegoeh S. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
This study aims to obtain a description of the surface area and volume problem solving profiles of class IX B students at SMP Negeri 1 Lore Tengah. This study uses a qualitative method with a qualitative descriptive approach. The research subjects were 3 students, namely students who had high, medium and low mathematical abilities based on the problem solving steps proposed by Polya. The research results obtained show that: (1) Students who have high mathematical abilities use all stages of Polya in solving problems of surface area and volume of cylinders. (2) Students who have moderate mathematical abilities have not been able to use all of Polya's stages in solving the problem of surface area and volume of cylinders, the stage in question is found in the re-examining stage. However, the subject gave his opinion by explaining using his own language why not re- examine the results of solving the problem given. (3) Students who have low mathematical abilities have not been able to go through all the stages of Polya in solving problems, the subject is only able to go through the stages of understanding the problem but the subject needs to read repeatedly and pay attention to the information contained in the problem repeatedly.